The Quest for more Research on Painful Diabetic Neuropathy. (1st September 2018) - Nawroth, P.P.; Bendszus, M.; Pham, M.; Jende, J.; Heiland, S.; Ries, S.; Schumann, C.; Schmelz, M.; Schuh-Hofer, S.; Treede, R.D.; Kuner, R.; Oikonomou, D.; et al.
Highlights: Lack of reliable epidemiological data concerning diabetic neuropathy. Rapid lowering of blood glucose levels can worsen symptoms associated with diabetic neuropathy. Findings from MR-neurography and histology suggest proximal primary nerve injury in diabetic polyneuropathy. There are no specific treatment options for diabetic neuropathy, with the drugs commonly used showing inconsistent results. Abstract: A 62-year-old diabetologist diagnosed himself to have diabetes type-2, with an HbA1c of 9.5. Five months after lifestyle intervention and a multi-drug approach, HbA1c was 6.3, systolic blood pressure was below 135 mmHg and BMI reduced to 27. But he suffered from severe painful diabetic neuropathy. Therefore he decided to visit his friend, a famous neuroscientist at an even more famous university. He asked him several plain questions: 1. What is the natural course of painful diabetic neuropathy? 2. Why do I have, despite almost normalizing HbA1c, more problems than before? 3. Are you sure my problems are due to diabetes or should we do a nerve biopsy? 4. Are there imaging techniques helpful for the diagnosis of this diabetic complication, starting in the distal nerve endings of the foot and slowly moving ahead? 5. Can you suggest any drug, specific and effective, for relieving painful diabetic neuropathy? This review will use the experts' answers to the questions of the diabetologist, not only to give a summary of the current knowledge, but even more to highlight areas of research needed for improving the fate of patients with painful diabetic neuropathy. Based on the unknowns, which exceed the knowns in diabetic neuropathy, a quest for more public support of research is made.